Divergent in vivo activity of non‐serotonergic and serotonergic VGluT3–neurones in the median raphe region - Domonkos, Andor (J Physiol, 2016)
KEY POINTS: The median raphe is a key subcortical modulatory centre involved in several brain functions, such as regulation of the sleep–wake cycle, emotions and memory storage. A large proportion of median raphe neurones are glutamatergic and implement a radically different mode of communication compared to serotonergic cells, although their in vivo activity is unknown. We provide the first description of the in vivo, brain state‐dependent firing properties of median raphe glutamatergic neurones identified by immunopositivity for the vesicular glutamate transporter type 3 (VGluT3) and serotonin (5‐HT). Glutamatergic populations (VGluT3+/5‐HT– and VGluT3+/5‐HT+) were compared with the purely serotonergic (VGluT3–/5‐HT+ and VGluT3–/5‐HT–) neurones. VGluT3+/5‐HT+ neurones fired similar to VGluT3–/5‐HT+ cells, whereas they significantly diverged from the VGluT3+/5‐HT– population. Activity of the latter subgroup resembled the spiking of VGluT3–/5‐HT– cells, except for their diverging response to sensory stimulation. The VGluT3+ population of the median raphe may broadcast rapidly varying signals on top of a state‐dependent, tonic modulation. ABSTRACT: Subcortical modulation is crucial for information processing in the cerebral cortex. Besides the canonical neuromodulators, glutamate has recently been identified as a key cotransmitter of numerous monoaminergic projections. In the median raphe, a pure glutamatergic neurone population projecting to limbic areas was also discovered with a possibly novel, yet undetermined function. In the present study, we report the first functional description of the vesicular glutamate transporter type 3 (VGluT3)‐expressing median raphe neurones. Because there is no appropriate genetic marker for the separation of serotonergic (5‐HT+) and non‐serotonergic (5‐HT–) VGluT3+ neurones, we utilized immunohistochemistry after recording and juxtacellular labelling in anaesthetized rats. VGluT3+/5‐HT– neurones fired faster, more variably and were permanently activated during sensory stimulation, as opposed to the transient response of the slow firing VGluT3–/5‐HT+ subgroup. VGluT3+/5‐HT– cells were also more active during hippocampal theta. In addition, the VGluT3–/5‐HT– population, comprising putative GABAergic cells, resembled the firing of VGluT3+/5‐HT– neurones but without any significant reaction to the sensory stimulus. Interestingly, the VGluT3+/5‐HT+ group, spiking slower than the VGluT3+/5‐HT– population, exhibited a mixed response (i.e. the initial transient activation was followed by a sustained elevation of firing). Phase coupling to hippocampal and prefrontal slow oscillations was found in VGluT3+/5‐HT– neurones, also differentiating them from the VGluT3+/5‐HT+ subpopulation. Taken together, glutamatergic neurones in the median raphe may implement multiple, highly divergent forms of modulation in parallel: a slow, tonic mode interrupted by sensory‐evoked rapid transients, as well as a fast one capable of conveying complex patterns influenced by sensory inputs.